The role of pulse oximetry in the diagnosis of cardiopulmonary complications of ERCP - Emin ALTIPARMAK; Orhan SEZGİN and Yıldıran SONGÜR and Yasemin KOŞAR and Ülkü SARITAŞ and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-